Determinants of inadequate energy intake among stunted children - Sylvie Puspita; Irwanto; Yuni Sufyanti Arief; Widati Fatmaningrum (Pediomaternal Nursing Journal, 2026)
Introduction: Stunting is a chronic growth disorder caused by prolonged inadequate nutrition and recurrent infections. Insufficient energy intake is a key factor contributing to impaired growth among stunted children. Objective: This study aimed to analyse the determinants associated with inadequate energy intake among stunted children and to compare these factors between tuberculosis and non-tuberculosis groups. Methods: An analytical observational study with a cross-sectional design was conducted among 80 stunted children aged 12–59 months in Jombang Regency, Indonesia. Participants were selected using consecutive sampling from community health centers. Data on child and maternal characteristics were collected using structured questionnaires and verified with the Maternal and Child Health Handbook. Stunting status was determined using height-for-age z-scores (HAZ) based on WHO standards. Energy intake was assessed using two non-consecutive 24-hour dietary recalls and categorized as adequate (≥80% RDA) or inadequate (<80% RDA). Data were analysed using the Kruskal–Wallis test with a significance level of P-value<.05. Results: Most children were aged >24 months (68.7%), female (58.7%), and had normal birth weight (72.5%). A total of 57.5% had adequate energy intake, while 42.5% were classified as inadequate. Significant determinants of energy intake included age (P-value<.001), birth weight (P-value=.004), maternal anemia during pregnancy (P-value=.037), and antenatal care (ANC) history (P-value=.005). No significant associations were found for gender (P-value=.991) and tuberculosis status (P-value=.653). Conclusion: Inadequate energy intake among stunted children is significantly influenced by both child and maternal factors. Strengthening maternal nutrition, improving ANC utilization, and promoting appropriate feeding practices are essential to support optimal energy intake and child growth. Keywords: anemia; energy intake; growth disorders; pregnant mothers; tuberculosis